High-strength waterproof fireproof thermal insulation composite board and manufacturing method thereof

By attaching a polystyrene particle layer of glue powder on the autoclaved aerated concrete slab and using ultrasonic vibration, the problems of poor waterproof performance and long construction period in the existing technology are solved, and the production of high-strength waterproof and fire-proof and thermal insulation composite board is realized, improving the production of high-strength waterproof and fire-proof composite board. The safety and comfort of the building enclosure structure.

CN119388557APending Publication Date: 2025-02-07GUANGDONG CHIYANG ENVIRONMENTAL PROTECTION BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the waterproof performance of the autoclaved aerated concrete products is poor, and the separation of the waterproof layer and the plate leads to poor bonding effect, and the construction period is long, which consumes a lot of manpower.

Method used

A high-strength waterproof and fire-proof and heat-insulating composite board is used to produce a high-strength waterproof and fire-proof composite board. By attaching a layer of glue powder polystyrene particles to the B03-level autoclaved aerated concrete board, the gas in the slurry is eliminated by ultrasonic vibration to form a dense waterproof and fire-proof layer.

Benefits of technology

It realizes excellent waterproof and fire-proof performance of composite panels, enhances compressive strength and mechanical properties, shortens construction time, and reduces workers' labor intensity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119388557A_ABST
    Figure CN119388557A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength waterproof fireproof thermal insulation composite board and a manufacturing method thereof. The manufacturing method comprises the following steps: 1) preparing a B03-grade autoclaved aerated concrete board as a thermal insulation substrate; 2) preparing rubber powder polyphenyl granule slurry; (3) hanging a B03-grade autoclaved aerated concrete plate on a saddle frame, and placing the plate in the middle of the mold frame by utilizing the saddle frame; 4) pouring the rubber powder polyphenyl granule slurry into a mold frame, performing ultrasonic vibration to compound the rubber powder polyphenyl granule layer on the surface of the plate, and pushing the mold frame into a curing chamber for curing; and (5) demolding after the green body is hardened, and continuously maintaining to form the high-strength waterproof and fireproof heat-insulating composite board. The high-strength waterproof fireproof thermal insulation composite board prepared by the method has good physical properties, light weight and high compressive strength, and the structural performance of the composite board is improved by the built-in steel bar mesh cage; the outer wall of the high-strength waterproof and fireproof thermal insulation composite board is the rubber powder polyphenyl granule waterproof and fireproof layer, so that the combustion performance and the waterproof performance of the composite board are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a high-strength waterproof, fireproof and thermal insulation composite board and a manufacturing method thereof. Background Art

[0002] At present, new wall materials, mainly autoclaved aerated concrete products, have developed rapidly, replacing traditional wall materials such as clay bricks and solid bricks, and becoming the main component of wall materials. Compared with traditional wall materials, autoclaved aerated concrete products have the characteristics of light weight and excellent thermal insulation performance, but their waterproof performance is poor. The existing technology waterproof layer and plate are separated. Due to the different materials, the compression and expansion coefficients are different, there is a risk of cracking, and the bonding effect between the layers is not good. The waterproof layer is generally applied at the construction site. On the one hand, the uniform thickness of the coating cannot be guaranteed, which greatly weakens the waterproof effect in some places. On the other hand, in most cases, the waterproof layer needs to be applied repeatedly, resulting in a long project construction period and a lot of manpower consumption.

[0003] There are also polystyrene particle lightweight sandwich partition boards on the market. They refer to lightweight sandwich wall panels with calcium silicate board as the surface material, cement and polystyrene particles, and mortar prepared with appropriate additions of fly ash, slag powder, admixtures, etc. as the base material. They also have good waterproof properties, but their compressive strength is low, and the internal base material does not have a steel mesh cage, so their structural performance is also poor. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention proposes a high-strength waterproof, fireproof and thermal insulation composite board and a manufacturing method thereof to solve the problems of poor bonding effect, poor waterproof effect and low compressive strength in the prior art.

[0005] The technical solution of the present invention is:

[0006] A method for manufacturing a high-strength waterproof, fireproof and thermal insulation composite board comprises the following steps:

[0007] 1) Prepare B03 grade autoclaved aerated concrete board as thermal insulation substrate;

[0008] 2) preparing rubber powder polystyrene particle slurry;

[0009] 3) hanging the B03 grade autoclaved aerated concrete board prepared in step 1) on a saddle frame, and placing the board in the middle of the mold frame by using the saddle frame;

[0010] 4) pouring the rubber powder polystyrene particle slurry obtained in step 2) into a mold frame, and ultrasonically vibrating the mold frame to form a composite rubber powder polystyrene particle layer on the surface of the board, and pushing the mold frame into a curing room for curing;

[0011] 5) After the blank is hardened, demould and continue to cure to form a high-strength waterproof, fireproof and thermal insulation composite board.

[0012] Furthermore, the production process of the B03 grade autoclaved aerated concrete board comprises the following steps:

[0013] 1) Weigh the raw materials by weight, including 10-30 parts of industrial solid waste, 20-55 parts of reinforcing phase, 10-20 parts of cement, 6-20 parts of lime, 0-0.2 parts of early strength agent, 0.1-0.2 parts of aluminum paste, and 0-6 parts of gypsum;

[0014] 2) adding water to the reinforcing phase and gypsum in step 1) and wet-grinding them in a ball mill to obtain a reinforcing phase slurry, wherein the water-to-solid ratio is 0.42 to 0.54;

[0015] 3) Adding water to the industrial solid waste in step 1) to prepare a slurry, wherein the industrial solid waste comprises 10-15 parts and water comprises 6-8 parts, and adjusting the pH of the slurry to 7-10 using 8%-15% quicklime on a dry basis to obtain a solid waste liquid slurry;

[0016] 4) mixing the aluminum powder paste in step 1) with water to obtain aluminum powder liquid, wherein the aluminum powder is 2.8-3.2 parts and the water is 20-30 parts;

[0017] 5) Make a steel mesh cage and hang it on the saddle frame, and fix the mesh cage on the drill rod;

[0018] 6) After stirring the reinforcement phase slurry prepared in step 2) and the solid waste liquid slurry prepared in step 3), cement, lime and early strength agent are added and mixed, and finally the aluminum powder liquid prepared in step 4) is added and stirred evenly to obtain the total slurry, which is poured, and a steel chisel is inserted into the mold using a saddle frame, and pre-cured at 40-60° C. for 120-220 minutes;

[0019] 7) After the pre-curing is completed, the steel chisel is pulled out using a saddle frame, and the steel mesh cage remains inside the green body. The green body is subjected to high-temperature and high-pressure steam curing for 7-10 hours to obtain a B03 grade autoclaved aerated concrete board.

[0020] Furthermore, the industrial solid waste in step 1) is at least one of POX acid slag or vanadium extraction tailings.

[0021] Furthermore, the reinforcing phase in step 1) is at least one of slag, fly ash and silica sand.

[0022] Furthermore, the early strength agent in step 1) is a calcium silicate hydrate seed early strength agent.

[0023] Furthermore, the preparation process of the rubber powder polystyrene particle slurry includes the following steps: weighing each component by weight, each component including polystyrene particle mixture: 10-20 parts, cement: 90-125 parts, fly ash: 55-80 parts, silica sand: 7.5-8.5 parts, cellulose: 0.03-0.08 parts, redispersible rubber powder: 2.0-2.6 parts, waterproofing agent: 0.2-0.26 parts, anti-cracking fiber: 0.3-0.6 parts, flame retardant: 1-3 parts, adding the above components into 48-65 parts by weight of water and mixing them evenly.

[0024] Furthermore, the polystyrene particle mixture is composed of a bulk density of 8 kg / m 3 Polystyrene particles A and bulk density of 17kg / m 3 The polystyrene particles B are uniformly mixed in a volume ratio of (0.5-2):(0.5-2) and crushed to a particle size of 0.2-0.8 mm.

[0025] Furthermore, the anti-cracking fiber is PP fiber or polypropylene fiber, and the fiber length is 8-10 mm.

[0026] Furthermore, the waterproofing agent is a silicone waterproofing agent, model number is SEAL80.

[0027] Furthermore, the flame retardant is magnesium hydroxide or antimony trioxide.

[0028] Furthermore, the cellulose is hydroxypropyl methylcellulose.

[0029] The high-strength waterproof, fireproof and thermal insulation composite board is prepared by the method.

[0030] The beneficial effects of the present invention are as follows:

[0031] 1. The present invention relates to a high-strength waterproof, fireproof and heat-insulating composite board and a method for making the same. The method of the present invention first produces a B03-grade autoclaved aerated concrete board, and then attaches a glue powder polystyrene particle layer to the outer wall of the B03-grade autoclaved aerated concrete board. Compared with a single concrete board in the prior art, the composite board prepared by the method of the present invention has excellent waterproof and fireproof properties; and a steel mesh cage is arranged inside the B03-grade autoclaved aerated concrete board, which enhances the compressive strength and mechanical properties of the composite board, and further improves the safety and comfort of the building envelope structure.

[0032] 2. The polystyrene powder waterproof and fireproof layer of the present application is cast and formed, with uniform thickness, uniform coating, strong adhesion, small drying shrinkage and water immersion linear deformation, and not easy to hollow or crack. And no manual on-site construction is required, which greatly shortens the construction time and reduces the labor intensity of workers.

[0033] 3. The rubber powder polystyrene particle waterproof and fireproof layer of the present application introduces ultrasonic vibration during pouring to remove gas in the slurry and improve the density of the rubber powder polystyrene particle layer.

[0034] 4. The method and technology described in this application are simple to operate and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation of the present invention, the following will briefly introduce the drawings required for use in the specific implementation. In all the drawings, each element or part is not necessarily drawn according to the actual scale.

[0036] Figure 1 It is a schematic structural diagram of the high-strength waterproof, fireproof and thermal insulation composite board of the present invention.

[0037] Description of the reference numerals: glue powder polystyrene particle layer 1, B03 grade autoclaved aerated concrete board 2. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above application content.

[0039] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.

[0040] Sources:

[0041] Magnesium hydroxide flame retardant: the index is Mg(OH)2 content ≥92%, whiteness ≥90, acid insoluble matter ≤4.5%, calcium oxide content ≤3%, D50(um) between 2 and 4, pH value between 9 and 11, purchased from Zhejiang Xusen Flame Retardant Co., Ltd., China, XS-MHB-3.

[0042] Antimony trioxide flame retardant: active ingredient content ≥99.5%, purchased from Shandong Yousuo Chemical Technology Co., Ltd.

[0043] Waterproofing agent: The indicators are bulk density 200-400g / L, pH between 7.0 and 8.5, purchased from Yilaitai SEAL80 from Shanghai Qishuo Industrial Co., Ltd., China.

[0044] Early strength agent: The indicator is bulk density 400-700kg / m 3, is calcium silicate hydrate seed early strength agent S7045, purchased from Nanjing Xinyi Synthetic Technology Co., Ltd.

[0045] Hydroxypropyl methylcellulose: Shandong Yiteng New Materials Co., Ltd.

[0046] POX acid leached slag: purchased from Guangdong Dongyue Environmental Protection Technology Co., Ltd.

[0047] Vanadium extraction tailings: purchased from Hunan Hongyuan New Energy Technology Co., Ltd.

[0048] Lime: The index is effective calcium oxide content ≥ 80%, 200 mesh pass rate is greater than or equal to 90%, purchased from Guangdong Hongtai Building Materials Co., Ltd.

[0049] Cement: The indicators are initial setting time of 110-150 minutes and final setting time of 190-260 minutes. It is purchased from China Resources Cement (Shantou) Co., Ltd.

[0050] Gypsum: The index is sulfur trioxide content ≥ 36%, purchased from Guangdong Yudean Jinghai Power Generation Co., Ltd.

[0051] Slag and fly ash: purchased from Guangdong Yudean Jinghai Power Generation Co., Ltd.

[0052] Silica sand: purchased from Guangdong Guishan Building Materials Co., Ltd.

[0053] Aluminum powder paste: The indicators are active aluminum content ≥90%, solid content ≥65%, particle size 200 mesh sieve pass rate ≥97%, purchased from Shandong Yinshuang New Materials Co., Ltd.

[0054] Redispersible rubber powder: vinyl acetate-ethylene redispersible rubber powder, purchased from Jiangsu Hongshi New Material Technology Co., Ltd.

[0055] Polypropylene fiber: The index is length 10mm, tensile strength>3500MPa, breaking strength ≥560MPa, elongation at break 10-50%, purchased from Taian Yilin New Materials Co., Ltd.

[0056] Other raw materials were purchased from the market.

[0057] Embodiment 1

[0058] 1.1 Weigh the raw materials of B03 grade autoclaved aerated concrete board, calculated by weight: 30 parts of industrial solid waste, 42 parts of reinforcing phase, 15 parts of cement, 10 parts of lime, 3 parts of gypsum, 0.1 parts of early strength agent, 0.1 parts of aluminum paste, the reinforcing phase is slag and silica sand, and the ratio of slag to silica sand is 1:1. The industrial solid waste is POX acid slag.

[0059] 1.2 Preparation of B03 grade autoclaved aerated concrete board, the specific steps are as follows:

[0060] 1) Weigh B03 grade autoclaved aerated concrete board raw materials according to weight and set aside;

[0061] 2) Add water to the reinforcing phase and gypsum, and wet grind them with a ball mill to obtain reinforcing phase slurry;

[0062] 3) adding water to the POX acid slag, and adding 8%-10% of quicklime on a dry basis to adjust the pH to 8-10, to obtain industrial solid waste slurry, which is pumped into a tank for storage;

[0063] 4) Add water to the aluminum powder paste and stir evenly to obtain aluminum powder liquid for later use;

[0064] 5) Make a steel mesh cage and hang it on the saddle frame, and fix the mesh cage on the drill rod;

[0065] 6) Add the reinforcing phase slurry prepared in step 2) and the industrial solid waste slurry prepared in step 3) into a pouring mixer, mix and stir to obtain a mixed slurry, control the temperature of the mixed slurry at 42° C., add an early strength agent, then add cement and quicklime powder into the pouring mixer, stir evenly, and finally add the aluminum powder liquid prepared in step 4) to obtain a total slurry, stir the total slurry for 20 seconds and then pour it into a mold. After pouring, use a saddle to insert the steel mesh cage prepared in step 5) into the mold injected with the slurry, and pre-cure it at 50° C. for 180 minutes;

[0066] 7) After pre-curing, the drill rod is pulled out using a saddle frame, the steel mesh cage remains inside the blank, and the drill rod hole remains on the blank; then demoulding and precise cutting are carried out, and then the blank is autoclaved and cured for 8 hours to obtain the B03 grade autoclaved aerated concrete board.

[0067] 1.3 Weigh the raw materials for preparing the rubber powder polystyrene particle slurry. The proportion of each raw material is as follows: 20 parts of polystyrene particle mixture, 110 parts of cement, 70 parts of fly ash, 60 parts of water, 8 parts of silica sand, 0.05 parts of cellulose, 2 parts of redispersible rubber powder, 0.2 parts of waterproofing agent, 0.3 parts of anti-cracking fiber, and 2 parts of flame retardant. The anti-cracking fiber is pp fiber, and the fiber length of the anti-cracking fiber is 10mm; the cellulose is hydroxypropyl methylcellulose; the waterproofing agent is silicone waterproofing agent, model SEAL80; the flame retardant is magnesium hydroxide.

[0068] 1.4 Prepare the rubber powder polystyrene particle slurry, the specific steps are as follows:

[0069] 1) The bulk density is 8kg / m 3 Polystyrene particles A and 17kg / m 3 The polystyrene particles B are uniformly mixed in a volume ratio of 1.5:0.8 to form a polystyrene particle mixture;

[0070] 2) crushing the polystyrene particle mixture obtained in step 1) into particles with a particle size of 80 mesh sieve residue ≤10% and an average particle size of 0.2 mm, adding a flame retardant, mixing evenly and setting aside to obtain a flame retardant polystyrene particle mixture;

[0071] 3) First, cement, silica sand, fly ash, water, anti-cracking fiber and waterproofing agent are placed in a mortar mixer and stirred and mixed, then fly ash, redispersible rubber powder and cellulose are added to the mortar mixer, and the mixture is stirred evenly, and finally the flame retardant polystyrene particle mixture obtained in step 2) is added, and the mixture is stirred for 20 minutes to obtain a rubber powder polystyrene particle slurry.

[0072] 1.5 Preparation of high-strength waterproof, fireproof and thermal insulation composite panels, the steps are as follows:

[0073] 1) Insert the drill rod into the B03 grade autoclaved aerated concrete plate with a drill hole and fix it to the saddle frame;

[0074] 2) Place the fixed B03 grade autoclaved aerated concrete slab in the middle of the formwork;

[0075] 3) Pour the glue powder polystyrene particle slurry into the mold frame, and spread the slurry on both sides of the B03 grade autoclaved aerated concrete slab;

[0076] 4) Use ultrasonic vibration to vibrate the rubber powder polystyrene particle slurry to expel the internal gas;

[0077] 5) Push the mold frame into the curing room for curing for 200 minutes;

[0078] 6) Cut after demoulding and continue to maintain in a natural environment for more than 10 days to obtain a high-strength waterproof, fireproof and thermal insulation composite board. The structure of the high-strength waterproof, fireproof and thermal insulation composite board prepared by the method described in this embodiment is as follows: Figure 1 shown.

[0079] Embodiment 2

[0080] The steps 1.3 of weighing raw materials for preparing rubber powder polystyrene particle slurry and 1.4 of preparing rubber powder polystyrene particle slurry in Example 1 are modified as follows: the industrial solid waste is replaced by vanadium extraction tailings, and the remaining steps are the same as those in Example 1.

[0081] 2.1 Weigh the raw materials for preparing the rubber powder polystyrene particle slurry. The proportion of each raw material is as follows: 20 parts of polystyrene particle mixture, 110 parts of cement, 70 parts of fly ash, 60 parts of water, 8 parts of silica sand, 0.05 parts of cellulose, 2 parts of redispersible rubber powder, 0.2 parts of waterproofing agent, 0.3 parts of anti-cracking fiber, and 2 parts of flame retardant. The anti-cracking fiber is polypropylene fiber, and the fiber length of the anti-cracking fiber is 8mm; the cellulose is hydroxypropyl methylcellulose; the waterproofing agent is silicone waterproofing agent, and the model is SEAL80. The flame retardant is antimony trioxide.

[0082] 2.2 Preparation of rubber powder polystyrene particle slurry, the specific steps are as follows:

[0083] 1) The bulk density is 8kg / m 3 Polystyrene particles A and 17kg / m 3 The polystyrene particles B are uniformly mixed in a volume ratio of 2:0.5 to form a polystyrene particle mixture;

[0084] 2) crushing the coarse polystyrene particles obtained in step 1) into particles with a 20-mesh sieve residue of ≤10% and an average particle size of 0.8 mm, adding a flame retardant, mixing evenly and setting aside to obtain a flame retardant polystyrene particle mixture;

[0085] 3) First, cement, silica sand, fly ash, water, anti-cracking fiber and waterproofing agent are placed in a mortar mixer and stirred and mixed, then fly ash, redispersible rubber powder and cellulose are added to the mortar mixer, and the mixture is stirred evenly, and finally the flame retardant polystyrene particle mixture obtained in step 2) is added, and the rubber powder polystyrene particle slurry is obtained after stirring for 15 minutes.

[0086] Embodiment 3

[0087] The steps 1.3 of weighing raw materials for preparing rubber powder polystyrene particle slurry and 1.4 of preparing rubber powder polystyrene particle slurry in Example 1 are modified as follows: the industrial solid waste is a mixture of POX acid slag and vanadium extraction tailings, the ratio of POX acid slag to vanadium extraction tailings is 1:1, and the remaining steps are the same as in Example 1.

[0088] 3.1 Weigh the raw materials for preparing the rubber powder polystyrene particle slurry. The proportion of each raw material is as follows: 20 parts of polystyrene particle mixture, 110 parts of cement, 70 parts of fly ash, 60 parts of water, 8 parts of silica sand, 0.05 parts of cellulose, 2 parts of redispersible rubber powder, 0.2 parts of waterproofing agent, 0.3 parts of anti-cracking fiber, and 2 parts of flame retardant. The anti-cracking fiber is polypropylene fiber, and the fiber length of the anti-cracking fiber is 8mm; the cellulose is hydroxypropyl methylcellulose; the waterproofing agent is silicone waterproofing agent, and the model is SEAL80. The flame retardant is antimony trioxide.

[0089] 3.2 Preparation of rubber powder polystyrene particle slurry, the specific steps are as follows:

[0090] 1) The bulk density is 8kg / m 3 Polystyrene particles A and 17kg / m 3 The polystyrene particles B are uniformly mixed in a volume ratio of 0.5:2 to form a polystyrene particle mixture;

[0091] 2) The coarse polystyrene particles obtained in step 1) are crushed into particles with a 40-mesh sieve residue of ≤10% and an average particle size of 0.4 mm, and a flame retardant is added and mixed evenly for later use to obtain a flame retardant polystyrene particle mixture;

[0092] 3) First, cement, silica sand, fly ash, water, anti-cracking fiber and waterproofing agent are placed in a mortar mixer and stirred and mixed, then fly ash, redispersible rubber powder and cellulose are added to the mortar mixer, and the mixture is stirred evenly, and finally the flame retardant polystyrene particle mixture obtained in step 2) is added, and the rubber powder polystyrene particle slurry is obtained after stirring for 15 minutes.

[0093] Example 4 Performance Verification

[0094] Comparative Example 1

[0095] Only the autoclaved aerated concrete board, the formula and the production steps are the same as 1.1 and 1.2 in the first embodiment.

[0096] Comparative Example 2

[0097] Only the glue powder polystyrene particle board is cast, and the formula and production steps are the same as 1.3 and 1.4 in Example 1.

[0098] Comparative Example 3

[0099] The formula and production steps are the same as those of Example 1, except that no steel mesh cage is placed in the autoclaved aerated concrete slab.

[0100] Comparative Example 4

[0101] The formula and production steps are the same as those of Example 1, except that ultrasonic vibration is not performed after pouring the glue powder polystyrene particle slurry.

[0102] The performance of Examples 1 to 3 and Comparative Examples 1 to 4 was verified, and the verification results are shown in Table 1.

[0103] Table 1 Performance test results of seven composite panels

[0104]

[0105] From the data in Table 1, it can be seen that the high-strength waterproof, fireproof and thermal insulation composite board with B03 autoclaved aerated concrete board as the substrate and the composite glue powder polystyrene particle waterproof and fireproof layer on the substrate has good physical properties. It is not only light in weight and high in compressive strength, but also has good structural properties due to the steel mesh cage inside the B03 autoclaved aerated concrete board. On the other hand, after the two materials are composited, their combustion performance is improved and the waterproof performance is also greatly improved. By comparison, it is found that the introduction of ultrasonic vibration into the glue powder polystyrene particle slurry during pouring can remove the gas in the slurry, making the glue powder polystyrene particle layer structure dense, which is beneficial to improve the waterproof performance of the high-strength waterproof, fireproof and thermal insulation composite board.

[0106] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments. On the basis of the present invention, some modifications or improvements can be made thereto, which is obvious to those skilled in the art. Therefore, these modifications or improvements made on the basis of not departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for manufacturing a high-strength waterproof, fireproof and thermal insulation composite board, characterized in that: The following steps are involved: 1) Prepare B03 grade autoclaved aerated concrete board as thermal insulation substrate; 2) preparing rubber powder polystyrene particle slurry; 3) hanging the B03 grade autoclaved aerated concrete board prepared in step 1) on a saddle frame, and placing the board in the middle of the mold frame by using the saddle frame; 4) pouring the rubber powder polystyrene particle slurry obtained in step 2) into a mold frame, and ultrasonically vibrating the mold frame to form a composite rubber powder polystyrene particle layer on the surface of the board, and pushing the mold frame into a curing room for curing; 5) After the blank is hardened, demould and continue to cure to form a high-strength waterproof, fireproof and thermal insulation composite board.

2. The method according to claim 1, characterized in that: The production process of the B03 grade autoclaved aerated concrete board comprises the following steps: 1) Weigh the raw materials by weight, including 10-30 parts of industrial solid waste, 20-55 parts of reinforcing phase, 10-20 parts of cement, 6-20 parts of lime, 0-0.2 parts of early strength agent, 0.1-0.2 parts of aluminum paste, and 0-6 parts of gypsum; 2) adding water to the reinforcing phase and gypsum in step 1) and wet-grinding them in a ball mill to obtain a reinforcing phase slurry, wherein the water-to-solid ratio is 0.42 to 0.54; 3) Adding water to the industrial solid waste in step 1) to prepare a slurry, wherein the industrial solid waste comprises 10-15 parts and water comprises 6-8 parts, and adjusting the pH of the slurry to 7-10 using 8%-15% quicklime on a dry basis to obtain a solid waste liquid slurry; 4) mixing the aluminum powder paste in step 1) with water to obtain aluminum powder liquid, wherein the aluminum powder is 2.8-3.2 parts and the water is 20-30 parts; 5) Make a steel mesh cage and hang it on the saddle frame, and fix the mesh cage on the drill rod; 6) After stirring the reinforcement phase slurry prepared in step 2) and the solid waste liquid slurry prepared in step 3), cement, lime and early strength agent are added and mixed, and finally the aluminum powder liquid prepared in step 4) is added and stirred evenly to obtain the total slurry, which is poured, and a steel chisel is inserted into the mold using a saddle frame, and pre-cured at 40-60° C. for 120-220 minutes; 7) After the pre-curing is completed, the steel chisel is pulled out using a saddle frame, and the steel mesh cage remains inside the green body. The green body is subjected to high-temperature and high-pressure steam curing for 7-10 hours to obtain a B03 grade autoclaved aerated concrete board.

3. The method according to claim 2, characterized in that: The industrial solid waste in step 1) is at least one of POX acid slag or vanadium extraction tailings.

4. The method according to claim 2, characterized in that: The reinforcing phase in step 1) is at least one of slag, fly ash and silica sand.

5. The method according to claim 2, characterized in that: The early strength agent in step 1) is a calcium silicate hydrate seed early strength agent.

6. The method according to claim 2, characterized in that: The production process of the rubber powder polystyrene particle slurry, The method comprises the following steps: weighing each component by weight, wherein each component comprises 10-20 parts of a polystyrene particle mixture, 90-125 parts of cement, 55-80 parts of fly ash, 7.5-8.5 parts of silica sand, 0.03-0.08 parts of cellulose, 2.0-2.6 parts of redispersible rubber powder, 0.2-0.26 parts of a waterproofing agent, 0.3-0.6 parts of anti-cracking fibers and 1-3 parts of a flame retardant, adding each component into 48-65 parts of water by weight and mixing the mixture evenly.

7. The manufacturing method according to claim 5, characterized in that: The polystyrene particle mixture has a bulk density of 8 kg / m 3 Polystyrene particles A and bulk density of 17kg / m 3 The polystyrene particles B are uniformly mixed in a volume ratio of (0.5-2):(0.5-2) and crushed to a particle size of 0.2-0.8 mm.

8. The manufacturing method according to claim 5, characterized in that: The anti-cracking fiber is PP fiber or polypropylene fiber, and the fiber length is 8-10mm.

9. The manufacturing method according to claim 5, characterized in that: The flame retardant is magnesium hydroxide or antimony trioxide.

10. A high-strength waterproof, fireproof and thermal insulation composite board prepared by the method according to any one of claims 1 to 9.